Methodology to determine the socioeconomic impact and ecosystem services loss caused by ravines and gullies - Kuhn, Caiubi Emanuel Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Gullies and ravines affect human life and the environment in many countries around the world. However, few studies have evaluated the impacts of damage caused by these large linear erosions and clarified their parameters of influence. In this context, the main objectives of this thesis were to identify and systematize the economic impacts and ecosystem services caused by ravines and gullies, aiming to propose a methodology for valuation, in addition to performing an analysis on which erosions should be prioritized for remediation. The methodological path that was adopted consisted of a) a global bibliographic review carried out in the Scopus, Web of Science and Dimensions databases, where more than 120 articles from 27 countries that addressed and evaluated these different types of impacts were identified; b) an analysis of official civil defence records on the impacts of ravines and gullies in Brazil, based on data from the Brazilian Civil Defense Integrated Information System (S2ID), combined with a bibliographic review; c) an application of the valuation methodology in a case study of brownfields caused by ravines and gullies that was conducted in the city of Bauru (Brazil), considering environmental damage, such as costs related to land restoration and erosion control, destruction of infrastructure, losses economic and income losses related to property and urban property taxes; and d) an adaptation of the Tailored Improvement of Brownfield Regeneration in Europe (TIMBRE) method for the analysis and classification of areas affected by linear erosion in the city of Bauru, specifically for erosion analysis to identify priority areas for remediation. Based on the results of the global bibliographic review, the possible types of impacts that can be caused by gullies and ravines and how they can be valued can be systematized. The review also indicated that the greatest impacts are registered in South America, Africa, China and India, related to characteristics of the physical environment, extreme events and disorderly land occupation. In Brazil, civil defence data show an increasing trend in the number of disasters related to ravines and gullies in the last decade (2011-2020), totalling 76 records in this period. However, only 24 of these records contained information on the impacts caused, which added up to an estimated loss of US$54 million. The spatial distribution of disasters related to linear erosion in Brazil suggests a connection between the development of ravines and gullies and the country's agricultural frontier, especially in the North and Midwest regions, including the Cerrado and Amazon Forest biomes, where the greatest changes in land use occurred between the end of the 20th century and the beginning of the 21st century. Based on the methodological proposal that was elaborated considering the global bibliographic review, a case study was conducted in the city of Bauru, Brazil, to carry out the valuation of impacts. The analyses indicate that the total damage in the three analysed areas over two decades exceeded US$ 173 million and was mainly related to losses due to the abandonment of the area. Urban areas affected by ravines and gullies pose problems that are similar to those of brownfields, creating urban voids. Therefore, the TIMBRE method was adapted to analyse areas affected by ravines and gullies, demonstrating a correlation between erosion and urban expansion. With the proposed methodology, the Quinta da Bela Olinda area was identified as the location with the highest scores in the three classifications, being the location with the greatest potential for business development, the most attractive brownfield and the area with the highest environmental risk. This area should, therefore, be prioritized by public management for remediation. Although the implementation of the assessment is challenging due to the large number of different forms of possible impacts related to environmental, economic and social changes, based on the results of this work, it is concluded that the proposed valuation method facilitates the identification and demonstration of the damages. On the other hand, the adaptation of the Timbre Method for ravines and gullies proved to be a great tool that assisted in decision-making about which erosions should be a priority for remediation. The set of results obtained in the thesis can promote management tools for disaster management and land use management in cities, helping public managers and the community to make more assertive decisions regarding the construction of public policies for the remediation of affected areas through ravines and gullies.

Voçorocas e ravinas afetam a vida humana e o meio ambiente em muitos países do mundo. No entanto, poucos estudos avaliaram os impactos dos danos causados por essas grandes erosões lineares e esclareceram seus parâmetros de influência. Neste contexto, os principais objetivos desta tese foram identificar e sistematizar os impactos econômicos e nos serviços ecossistêmicos causados por ravinas e voçorocas, visando propor uma metodologia para valoração, além de realizar uma análise sobre quais erosões devem ser priorizadas para remediação. O caminho metodológico adotado consistiu em: a) Uma revisão bibliográfica global realizada nas bases de dados Scopus, Web of Science e Dimensions, onde foram identificados mais de 120 artigos de 27 países que abordaram e avaliaram esses diferentes tipos de impactos; b) Análise dos registros oficiais na defesa civil sobre impactos de ravinas e voçorocas no Brasil, com base nos dados do Sistema Integrado de Informações da Defesa Civil Brasileira (S2ID), aliada a uma revisão bibliográfica; c) Aplicação da metodologia de valoração em um estudo de caso realizado na cidade de Bauru (Brasil), para brownfields causados por ravinas e voçorocas, considerando danos ambientais, como custos relacionados à restauração de terras e controle de erosão, destruição de infraestrutura, perdas econômicas e perdas de renda relacionadas a impostos prediais e prediais urbanos; e d) Adaptação do método Tailored Improvement of Brownfield Regeneration in Europe (TIMBRE) para a análise e classificação de áreas afetadas por erosão linear na cidade de Bauru, para análise de erosões visando identificar áreas prioritárias para remediação. Os resultados da revisão bibliográfica global permitiram a sistematização dos tipos possíveis de impactos que podem ser causados por voçorocas e ravinas e como eles podem ser valorados. A revisão também indicou que os maiores impactos são registrados na América do Sul, África, China e Índia, relacionados a características do meio físico, eventos extremos e ocupação desordenada do solo. No Brasil, os dados da defesa civil mostram uma tendência crescente no número de desastres relacionados a ravinas e voçorocas na última década (2011-2020), totalizando 76 registros nesse período. No entanto, apenas 24 desses registros continham informações sobre os impactos causados, que somaram uma perda estimada de US$ 54 milhões. A distribuição espacial dos desastres relacionados à erosão linear no Brasil sugere uma conexão entre o desenvolvimento de ravinas e voçorocas e a fronteira agrícola do país, especialmente nas regiões Norte e Centro-Oeste, incluindo os biomas Cerrado e Floresta Amazônica, onde ocorreram as maiores mudanças no uso da terra entre o final do século XX e o início do século XXI. Com base na proposta metodológica elaborada considerando a revisão bibliográfica global, foi realizado um estudo de caso na cidade de Bauru, Brasil, para realizar a valoração de impactos. As análises indicam que o dano total em três áreas analisadas ultrapassa US$ 173 milhões em duas décadas e está relacionado principalmente a perdas pelo abandono da área. As áreas urbanas afetadas por ravinas e voçorocas representam problemas semelhantes aos brownfields, criando vazios urbanos. Portanto, o método TIMBRE foi adaptado para a análise das áreas afetadas por ravinas e voçorocas, demonstrando uma correlação entre erosão e expansão urbana. A metodologia proposta identificou a área da Quinta da Bela Olinda como o local que possui as maiores pontuações nas três classificações, sendo o local com maior potencial para o desenvolvimento de negócios, o brownfield mais atrativo e também a área com maior risco ambiental. Essa área deve, portanto, ser priorizada pela gestão pública para remediação. Embora a implementação da avaliação seja desafiadora devido ao grande número de diferentes formas de possíveis impactos relacionados a mudanças ambientais, econômicas e sociais, os resultados deste trabalho concluem que o método de valoração proposto permite identificar e demonstrar os danos. Por outro lado, a adaptação do Método Timbre para ravinas e voçorocas mostrou-se uma ótima ferramenta para auxiliar na tomada de decisões sobre quais erosões devem ser prioritárias para remediação. O conjunto de resultados obtidos na tese pode fomentar ferramentas de gestão para o gerenciamento de desastres e gestão do uso da terra nas cidades, auxiliando gestores públicos e a comunidade a tomar decisões mais assertivas em relação à construção de políticas públicas para a remediação de áreas afetadas por ravinas e voçorocas.

Spalten und Schluchten beeinträchtigen in vielen Ländern der Welt das menschliche Leben und die Umwelt. Allerdings haben nur wenige Studien die Auswirkungen der durch diese großen linearen Erosionen verursachten Schäden bewertet und ihre Einflussparameter geklärt. In diesem Zusammenhang bestand das Hauptziel dieser Arbeit darin, die wirtschaftlichen Auswirkungen und Ökosystemleistungen, die durch Schluchten verursacht werden, zu identifizieren und zu systematisieren. Ziel war es, eine Bewertungsmethode vorzuschlagen und außerdem zu analysieren, welche Erosionen bei der Sanierung priorisiert werden sollten. Der gewählte methodische Weg bestand aus a) einer globalen bibliografischen Überprüfung, die in den Datenbanken Scopus, Web of Science und Dimensions durchgeführt wurde, wobei mehr als 120 Artikel aus 27 Ländern identifiziert wurden, die diese verschiedenen Arten von Auswirkungen thematisierten und bewerteten, b) eine Analyse der offiziellen Aufzeichnungen des Zivilschutzes über die Auswirkungen von Schluchten in Brasilien, basierend auf Daten des brasilianischen Zivilschutz-Integrierten Informationssystems (S2ID), kombiniert mit einer bibliografischen Überprüfung, c) der Anwendung der Bewertungsmethodik in einer Fallstudie in der Stadt Bauru (Brasilien) für Brachflächen, die durch Schluchten verursacht wurden, unter Berücksichtigung von Umweltschäden, wie z. B. Kosten im Zusammenhang mit der Wiederherstellung von Land und Erosionsschutz, der Zerstörung von Infrastruktur, wirtschaftlichen Verlusten und Einkommensverlusten im Zusammenhang mit Grundsteuern und städtischem Eigentum und d) eine Anpassung der Tailored Improvement of Brownfield Regeneration in Europe (TIMBRE)-Methode zur Analyse und Klassifizierung von Gebieten, die von linearer Erosion in der Stadt Bauru betroffen sind, insbesondere für die Erosionsanalyse, um vorrangige Gebiete für die Sanierung zu identifizieren. Die Ergebnisse der globalen bibliografischen Überprüfung erlauben eine Systematisierung möglicher Arten von Auswirkungen, die durch Schluchten verursacht werden können und wie diese bewertet werden können. Die Überprüfung ergab auch, dass die größten Auswirkungen in Südamerika, Afrika, China und Indien zu verzeichnen sind und mit Merkmalen der physischen Umwelt, Extremereignissen und ungeordneter Landbesetzung zusammenhängen. In Brasilien zeigen die Daten des Zivilschutzes einen steigenden Trend bei der Zahl der Katastrophen im Zusammenhang mit Schluchten im letzten Jahrzehnt (2011–2020), wobei es in diesem Zeitraum insgesamt 76 Rekorde gab. Allerdings enthielten nur 24 dieser Aufzeichnungen Informationen über die verursachten Auswirkungen, was zu einem geschätzten Schaden von 54 Millionen US-Dollar führte. Die räumliche Verteilung von Katastrophen im Zusammenhang mit linearer Erosion in Brasilien deutet auf einen Zusammenhang zwischen der Entwicklung von Schluchten und der landwirtschaftlichen Grenze des Landes hin, insbesondere in den Regionen im Norden und Mittleren Westen, einschließlich der Biome Cerrado und Amazonaswald, wo zwischen dem Ende des 20. und dem Beginn des 21. Jahrhunderts die größten Veränderungen in der Landnutzung stattfanden. Basierend auf dem methodischen Vorschlag, der unter Berücksichtigung der globalen bibliographischen Überprüfung erarbeitet wurde, wurde eine Fallstudie in der Stadt Bauru, Brasilien, durchgeführt, um die Auswirkungen zu bewerten. Die Analysen zeigen, dass der Gesamtschaden in den drei analysierten Gebieten über zwei Jahrzehnte 173 Millionen US-Dollar überstieg und hauptsächlich auf das Aufgeben der Gebiets zurückzuführen war. Von Schluchten betroffene städtische Gebiete zeigen ähnliche Probleme und führen zu städtischen Leerstand. Daher wurde die TIMBRE-Methode angepasst, um von Schluchten betroffene Gebiete zu analysieren und einen Zusammenhang zwischen Erosion und Stadterweiterung aufzuzeigen. Mit der vorgeschlagenen Methodik wurde das Gebiet Quinta da Bela Olinda als Standort mit den höchsten Bewertungen in den drei Klassifizierungen identifiziert, da es sich um den Standort mit dem größten Potenzial für die Geschäftsentwicklung, die attraktivste Gegend, aber das Gebiet mit dem höchsten Umweltrisiko handelt. Daher sollte dieser Bereich von der öffentlichen Verwaltung bei der Sanierung priorisiert werden. Obwohl die Durchführung der Bewertung aufgrund der Vielzahl unterschiedlicher Formen möglicher Auswirkungen im Zusammenhang mit ökologischen, wirtschaftlichen und sozialen Veränderungen eine Herausforderung darstellt, kommt man auf Grundlage der Ergebnisse dieser Arbeit zu dem Schluss, dass die vorgeschlagene Bewertungsmethode die Identifizierung und den Nachweis der Schäden erleichtert. Andererseits erwies sich die Anpassung der Timbre-Methode für Schluchten als großartiges Hilfsmittel, das bei der Entscheidungsfindung darüber, welche Erosionen bei der Sanierung Vorrang haben sollten, hilfreich war. Die in der Dissertation erzielten Ergebnisse können Managementinstrumente für das Katastrophenmanagement und das Landnutzungsmanagement in Städten fördern und öffentlichen Entscheidungsträgern und der Gemeinde dabei helfen, durchsetzungsfähigere Entscheidungen hinsichtlich der Gestaltung öffentlicher Richtlinien zur Sanierung betroffener Gebiete durch Schluchten zu treffen.
Metodologia para determinar o impacto socioeconômico e a perda de serviços ecossistêmicos causados por ravinas e voçorocas
Methodik zur Bestimmung der sozioökonomischen Auswirkungen und des Verlusts von Ökosystemleistungen durch Spalten und Schluchten
Keywords: Evaluation; Impact analysis; Civil defense; Brownfields; Soil; Avaliação; Análise de impacto; Defesa civil; Solo; Wirkungsanalyse; Zivilschutz; Brachflächen; Boden